Design of DIALux Based Lighting Controller for Energy Savings - Brota Mitra, Ananya; Saha, Amrit; Jana, Roni; Roy, Amartya (International Journal of Computer Sciences and Engineering, 2025)
The paper aims in integration of daylight and artificial lighting simulation for efficient lighting scheme in order to save energy as almost 30% to 40% of our energy consumption depends upon lighting scheme. A room with known dimension is designed in DIALux and is mounted with fluorescent tubular lamp to light up the room and to maintain considered average illuminance and uniformity of the classroom remaining uniform throughout the room and the artificial lights are accordingly grouped in different control groups with different dimming values in order to maintain uniformity and save energy from the throughout system. The simulation is done using DIALux and lighting parameters ( Eavg, Emin, Emax and uniformity) are obtained from the isoline diagram and electrical parameters (Wattage) are obtained. The daylight is allowed to enter the room and accordingly artificial light is controlled leading to energy efficient Lighting Controller where the dimming values of the lamps changes with the change in intensity of the daylight as it is dynamic in nature. Data is obtained for three different time of the year with different sky conditions viz. Overcast Sky, Clear Sky and Mixed sky.